Diasporic Life Experienced by the Main Character in Jessica Jung’s Shine - Cintya Arum Pawesti (Faculty of Humanities, 2024)
Shine is a diaspora novel by Jessica Jung that was published in 2020. The novel tells about the life of Rachel Kim as a diasporic subject in America and Korea. The novel contains diasporic themes regarding alignment, longing, and cultural differences in the host country experienced by diasporic subjects. Through the main character in the novel, this research aims to find the difficulties and strategies possessed by this character as a diasporic subject. The main character in this novel also experienced several stages of living as a diasporic subject. In conducting this research, the author applies the postcolonialism theory from Homi K. Bhabha. The results of this research show that the hybridity possessed by the main character at the end of the story is the result of the form of mimicry that the main character does. Interpretation of the data shows that hybridity and mimicry make the main character a cultural hybrid product. According to the topic of the discussion above, three research questions are raised, which are diasporic problems experienced by the novel's main character and how it is related to the contextual conditions of foreign immigrants in America and Korea. Lastly, collaborating on the author's point of view in this novel is also necessary because the novel is related to the author's life experiences as an immigrant. This research uses qualitative research. The analysis in this research was prepared using a narrative structure from the novel as primary data and other sources from books, journals, and the internet as secondary data. The data found in the novel shows the main character's struggles in living as a diaspora and her strategies she chooses to survive in the host country. The results of this research show that the main character in the novel experiences several stages in her life as a diasporic subject. The main character, Rachel, experiences discrimination and racism in America. Then, she moved to Korea to debut as a K-pop idol. In Korea, the main character also experiences thesame discrimination as in America. The main character subconsciously considers America as her homeland and longs for America. It can be said that the main character has felt unhomly feelings towards these two countries. To adapt to Korea, the main character uses survival strategies to survive in Korea as her host country. She tried to imitate the K-pop idol and fulfill the Korean stereotype of a K-pop idol with the intention that she would be accepted by society. Even though she mimics the host culture, she still wants to maintain differences on the other side. The crossed lines between both cultures have made the main character a product of cultural hybridity, which is Korean and American. Jessica Jung realistically describes the actual social conditions of the Korean immigrants in America and the foreign immigrants in Korea. The realistic depiction of Jung in her storyline portrays the main problem of the immigrant through the character conflicts. Jung wanted to emphasize the difficulties felt by Korean immigrants getting into America and foreign immigrants getting into Korea. Jung also emphasized that to escape the difficulties and discrimination she felt in two countries. She tried to debut as a K-pop idol as a survival strategy. By becoming a K-pop idol and using her hybridity, she can be recognized by both societies.
Reupload file repository 18 februari 2026_Arif/Halima
Keywords: Diasporic Life; Jessica Jung’s Shine